2008
DOI: 10.1016/j.neuroscience.2007.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Acute induction of epileptiform discharges by pilocarpine in the in vitro isolated guinea-pig brain requires enhancement of blood–brain barrier permeability

Abstract: Systemic application of the muscarinic agonist, pilocarpine, is commonly utilized to induce an acute status epilepticus that evolves into a chronic epileptic condition characterized by spontaneous seizures. Recent findings suggest that the status epilepticus induced by pilocarpine may be triggered by changes in the blood-brain barrier (BBB) permeability. We tested the role of the BBB in an acute pilocarpine model by using the in vitro model brain preparation and compared our finding with in vivo data. Arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 56 publications
(78 reference statements)
2
54
0
Order By: Relevance
“…This observation was supported by another study [60] in which it was found that acute induction of epileptiform discharges by pilocarpine in the in vitro isolated guinea-pig brain requires enhancement of blood-brain barrier permeability. Cytokines can increase the expression of adhesion molecules and selectins (such as ICAM-1, VCAM-1, chemokines, and their receptors) on endothelial and epithelial cells in the BBB and blood-CSF barrier [61].…”
Section: Does Uncontrolled Inflammation Drive the Chronic Progressionsupporting
confidence: 55%
See 1 more Smart Citation
“…This observation was supported by another study [60] in which it was found that acute induction of epileptiform discharges by pilocarpine in the in vitro isolated guinea-pig brain requires enhancement of blood-brain barrier permeability. Cytokines can increase the expression of adhesion molecules and selectins (such as ICAM-1, VCAM-1, chemokines, and their receptors) on endothelial and epithelial cells in the BBB and blood-CSF barrier [61].…”
Section: Does Uncontrolled Inflammation Drive the Chronic Progressionsupporting
confidence: 55%
“…Recent compelling research has highlighted the involvement of BBB permeability in the development of epilepsy. Immune-mediated damage to the nervous system is emerging as an important contributor to epileptogenesis, both directly through inflammation and indirectly by causing BBB leakage [60,93,94]. Other factors contributing to the alteration of brain homeostasis and generation of seizures from BBB leakage may include albumin [59,95] or epileptogenic agents such as glutamate, which are more concentrated in serum than brain [96,97].…”
Section: Do Uncontrolled Inflammation Bbb Damage and Seizures Form mentioning
confidence: 99%
“…BBB disruption (BBBD) causes seizures in animal models and human subjects [19, 45, 46, 48, 50, 51, 85]. In particular, a model of temporal lobe epilepsy (pilocarpine, PILO) also depends on BBBD [19, 51, 84]. The currently accepted mechanism of BBBD-induced seizures predicts activation of adhesion molecules on endothelial cells and leukocytes [19].…”
Section: 3 the Blood-brain Barrier (Bbb)mentioning
confidence: 99%
“…Double-barreled glass pipettes recordings were utilized in the IWB to simultaneously record at the same site FPs, extracellular K + and protons (H + as a measure of extracellular pH) signals with ion-selective resins (de Curtis et al, 1998b;Librizzi et al, 2001;Gnatkovsky et al, 2008;Uva et al, 2008). Local application of BMI in the second layer of the PC was able to induce local interical spikes that spread from the PC to the lateral EC and to the hippocampal formation.…”
Section: Recording Brain Activity In the Iwbmentioning
confidence: 99%